2020
DOI: 10.1186/s12885-020-06914-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive factors for Taiwanese patients with advanced biliary tract cancer undergoing frontline chemotherapy with gemcitabine and cisplatin: a real-world experience

Abstract: Background: Chemotherapy with gemcitabine and cisplatin has been the standard of care in first-line chemotherapy for advanced biliary tract cancer (BTC) since the trial ABC-02 was published in 2010. We aimed to investigate the prognostic and predictive factors of this regimen in a cohort of Taiwanese patients with advanced BTC. Methods: A total of 118 patients with histologically confirmed BTC treated at Chang Gung Memorial Hospital at Linkou from 2012 to 2017 were retrospectively reviewed. Results: The median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Notably, a similarly conducted real-world study on Taiwanese patients [ 15 ], but treated with GemCis, reported almost identical data to ours.…”
Section: Discussionsupporting
confidence: 84%
“…Notably, a similarly conducted real-world study on Taiwanese patients [ 15 ], but treated with GemCis, reported almost identical data to ours.…”
Section: Discussionsupporting
confidence: 84%
“…Biliary tract cancers (BTCs) including intrahepatic cholangiocarcinoma (iCCA), extrahepatic cholangiocarcinoma (eCCA), gallbladder cancer, and ampullary cancer are a group of relatively rare cancers arising from the epithelium of the biliary tract [1][2][3][4] and have aggressive biological behavior, as they are diagnosed at an advanced stage with poor prognosis and have a high recurrence rate after primary surgery [5,6]. Gemcitabine and cisplatin have been the standard treatments in first-line chemotherapy since the ABC-02 trial was published in 2010 [7].…”
Section: Current Treatment For Biliary Tract Cancers (Btcs): Chemothementioning
confidence: 99%
“…Clinical trials have evaluated molecular targeted therapies in combination with chemotherapy; however, none of the completed phase III trials [8][9][10][11] and phase II studies [12][13][14][15] have demonstrated significant improvement in progression-free survival (PFS) and overall survival (OS) in patients with advanced BTCs [16]. Real word experience has confirmed the feasibility and safety of gemcitabine and cisplatin in advanced BTCs [6,17].…”
Section: Current Treatment For Biliary Tract Cancers (Btcs): Chemothementioning
confidence: 99%
“…Many studies have shown that in ammation is related to the occurrence, development and metastasis of malignant tumors [7][8][9][10][11]. Because the leukocyte count and various types of white blood cells are indicators of systemic in ammation and immune response, these values may be good candidate biomarkers for predicting aggressive tumors.…”
Section: Discussionmentioning
confidence: 99%